Salmonella transfer potential between tomatoes and cartons used for distribution - Topalcengiz, Zeynal; Friedrich, Loretta M.; Danyluk, Michelle D. (Elsevier, 2023)
Corrugated fiberboard boxes (cartons) can be reused during fresh market tomato packing and repacking. The fate of Salmonella on the new, used, and dirty tomato packaging cartons, and Salmonella transfer between toma-toes and new, used, and dirty packaging cartons was assessed. Mature green tomatoes or blank cartons were spot inoculated with cocktail of rifampicin-resistant Salmonella strains before touching cartons/tomatoes at 0, 1, or 24 h postinoculation. Tomatoes were placed on new, used, and dirty carton squares (5 by 5 cm) for 0, 1, and 7 days of contact at 12 degrees C and 25 degrees C with a relative humidity value of 85%. Transfer coefficients (TCs) were calculated for all conditions. Salmonella populations decreased following inoculation by 2-3 log units during 24 h drying regardless of storage temperature; the presence of debris enhanced survival at 12 degrees C. In general, the highest transfer rates occurred with wet inoculum. The highest Salmonella transfer was cal-culated for wet inoculated tomatoes with 7 days of contact time at 25 degrees C (TC = 14.7). Increasing contact time decreased TCs for new cartons, but increased TCs for used and dirty cartons. Regardless of carton condition or storage temperature, a greater population of Salmonella was transferred from tomatoes to cartons than from cartons to tomatoes. Salmonella transfer between tomatoes and cartons is highly dependent on moisture, with increased levels of moisture increasing transfer, highlighting the importance of harvesting and packing dry tomatoes.
Keywords: Contact Time; Inoculum Drying; Tomato Packing; Tomato Safety; Transfer Coefficient; Multistate Outbreak; Contamination; Disinfection; Survival